Pengaruh Penggunaan Catalytic Converter Tembaga Berlapis Mangan Terhadap Kadar Polutan Gas Buang Motor Bensin Empat Langkah - Warju(, ; Djoko Sungkono(2), (Teknika, 2006)
One of the efforts to decrease exhaust gas emission from four stroke gasoline engine is using cuprum (Cu) coated mangan (Mn) as active metal catalyst to reduce CO, HC and NOx emission. It is placed in exhaust system that is called catalytic converter.The experiment was carried out at Fuel and Internal Combustion Engine Laboratory Mechanical Engineering Departement ITS. In this experiment Honda Karisma X 125D engine was used. The test method is done by velocity gradient at full load (full open throttle valve). The test was carried out by comparing standard engine experiment and engine experiment with catalytic converter on exhaust system. The type of the test is desk test. Data analysis is done by using descriptive methods. The analysis shows that cuprum (Cu) coated mangan (Mn) as catalytic converter with 110 gr Cu + 90 gr Mn catalyst mass decreases vehicle emission that the greatest CO emission decrease at A/F 15 or exhaust gas temperature 273-340°C is up to 96,36%.